TINJAUAN SIYASAH SYAR’IYYAH TERHADAP PEDAGANG KAKI LIMA YANG MENGGUNAKAN FASILITAS UMUM DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Magfirah, Fadia; Sohrah, Sohrah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
The activity of street vendors is a sector of abuse of public facilities in the community which is rife and even has the potential to cause disruption to cleanliness, order, comfort and harm to the community. For this reason, this research is a qualitative field research with an empirical normative approach and a theological approach. The results of the study show that street vendors in Somba Opu District are still using public facilities as a means to sell, so the Government of Gowa Regency is carrying out various arrangements with the obligation for street vendors to have permits, outreach, provide land, and maintain order so that street vendors do not again destroying the order of the city. In addition, the use of public facilities by street vendors is very inconsistent with Islamic values ​​and ethics which are always honest, trustworthy or responsible, deceitful and keep promises.